Standard histological techniques systematically under‐estimate the size fish start spawning. Issue 6 (1st September 2022) - Prince, Jeremy; Harford, William J.; Taylor, Brett M.; Lindfield, Steven J.
Abstract: Beverton & Holt's (1957) functional definition of maturity in fish ( L 50 ), as being the size class in which 50% of individuals begin producing gametes in some proportion to body weight, is widely used in assessment models to estimate spawning stock biomass, and manage the minimum size of capture. Standardized histological techniques for estimating L 50 apply physiological definitions that identify cellular or hormonal markers indicating individuals are capable of producing gametes. Few studies have examined how those phases of gonadal development correlate with reproductive behaviour or reproductive output. We compare histological estimates of L 50 for 10 species of reef fish from Palau, with the size composition of catches, surveys and spawning aggregations, and interpret those comparisons with simulation modelling. Our study shows that the histological L 50 estimates coincide with the size species begin ontogenetically shifting between juvenile and adult habitat, and with the size the smallest individuals join spawning aggregations, but are ~15% smaller than the length at which we infer 50% of individuals begin joining spawning aggregations. This highlights a mismatch between the functional definition of L 50 assumed for assessment and management, and the physiological definitions developed for histological studies, which identify the beginning of a sub‐adult adolescent phase, rather than the end, when functional adulthood starts. This definitional mismatch could be causing stock assessments to systematically over‐estimate the reproductive output of fisheries. By considering fish behaviour, we hope to better align estimates of physiological maturation with the estimation of functional reproductive potential required for assessment and management.